Providing pharmacy support to housebound patients: learning from the COVID-19 pandemic. (1st April 2022) - Garfield, S F; Wheeler, C; Etkind, M; Ogunleye, D; Williams, M; Boucher, C; Taylor, A; Norton, J; Lloyd, J; Grimes, T; Kelly, D; Franklin, B D
Abstract: Introduction: Housebound patients may face challenges to their medicines management due to reduced household mobility and potential lack of access to healthcare services. Previous literature has explored the medication-related needs of housebound patients from pharmacists' perspectives (1-2). However little work has focussed on the patient/family perspective. In this study, we used data obtained from those staying at home as much as possible during the COVID-19 pandemic to fill this gap. Aim: To explore home medicine practices and safety for people who were housebound during the COVID19 pandemic and to create guidance, from the patient/family perspective, for enabling pharmacists to facilitate safe medicine practices for this population. Methods: Interviews were carried out with people who were taking at least one long term medication and met the criteria for 'shielding' and/or were over 70 years of age during the first wave of the COVID-19 pandemic in the UK and/or their family carers. Respondents were recruited through patient and public involvement representatives, the research team's networks, and support groups. Potential participants were approached via personal contact and social media. Interviews were conducted by telephone or video conferencing and participants asked about their medicines management while staying at home. Inductive thematic analysis was carried out. Patient and public involvement representatives were involved in the data analysis alongside the researchers. Results: Fifty people were interviewed (16 males, 34 females; mean age 68 years, range 26–93 years). Interview data suggested diversity of experiences of medicines management while staying at home. Some respondents reported no or little change, others an initial crisis followed by re-stabilisation, and others that the pandemic was a tipping point, exacerbating underlying challenges and having negative effects on their health and wellbeing. Medicine safety issues reported included omitted doses and less-effective formulations being used. Participants also described experiencing high levels of anxiety related to obtaining medicines, monitoring medicines and feeling at risk of contracting COVID-19 while accessing medicine-related healthcare services. Key factors identified as facilitating a smooth transition included patients' own agency, support from family, friends and community, good communication with pharmacy staff, continuity of pharmacy services and synchronisation of medicines supply so that a maximum of one collection/delivery was required each month. Conclusion: The study findings that we have presented relate to the UK only; this may limit the generalisability of our findings to other countries. Findings from Ireland are in the process of being analysed and will provide a basis of comparison. In addition, more females took part than males, despite efforts to address this. However, our findings suggest pharmacy staff can support medicines management for people who are housebound by synchronisation of medicines supply, delivering medicines where possible, developing/raising awareness of alternative means of communication, providing continuity of pharmacy services and signposting any community support available. References: (1) Kayyali R, Funnell G, Harrap N, Patel A. Can community pharmacy successfully bridge the gap in care for housebound patients? Research in Social and Administrative Pharmacy 2019;15:425-439. (2) Latif A, Mandane B, Anderson E, Barraclough C, Travis S. Optimizing medicine use for people who are homebound: an evaluation of a pilot domiciliary Medicine Use Review (dMUR) service in England. Integr Pharm Res Pract 2018;7:33-40.